DOI: 10.22215/etd/2015-10911
|View full text |Cite
|
Sign up to set email alerts
|

"Everything is in the Lab Book”: The Role of the Lab Book Genre in Writing, Knowledge-Making, and Identity Construction in Academic Medical Physics Labs

Abstract: This qualitative study explores the nature and functions of the lab book genre in the discipline of medical physics. Specifically, it investigates how the multimodal nature of the lab book facilitates knowledge-making and identity construction in an academic medical physics community located in a Canadian university. The study employs the theoretical framework of Writing, Activity, and Genre Research (WAGR) in combination with the theoretical notions of communities of practice (CoP) and multimodality. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…The illustrative example discussed in the article is part of a longitudinal multiphase qualitative research project, which focused on the culture of a group of medical physicists working at a university medical physics unit who were at different stages of their careers at the time of the study (Doody, 2015). The research project followed an emergent research design, which enabled us to be responsive to unforeseen events occurring during the research process (e.g., Charmaz, 2006, p. 25) and allowed us to approach the research process as generative; that is, working with data revealed new questions, hypotheses, and insights, which were integrated into the research agenda (and at times shifted it), so that findings were corroborated through the subsequent stages of data generation and analysis (Schwandt, 2001, p. 100).…”
Section: Methodsmentioning
confidence: 99%
“…The illustrative example discussed in the article is part of a longitudinal multiphase qualitative research project, which focused on the culture of a group of medical physicists working at a university medical physics unit who were at different stages of their careers at the time of the study (Doody, 2015). The research project followed an emergent research design, which enabled us to be responsive to unforeseen events occurring during the research process (e.g., Charmaz, 2006, p. 25) and allowed us to approach the research process as generative; that is, working with data revealed new questions, hypotheses, and insights, which were integrated into the research agenda (and at times shifted it), so that findings were corroborated through the subsequent stages of data generation and analysis (Schwandt, 2001, p. 100).…”
Section: Methodsmentioning
confidence: 99%
“…As stated earlier in this chapter, learning to become an effective disciplinary writer requires more than the acquisition of a set of skills and knowledge (Blakeslee, 1997;Dall'Alba & Sandberg, 2006;Gee, 2005;Poe et al, 2010); writing takes place within a social and cultural context (Collins et al, 1989;Doody, 2015;Maher, 2008) and in the context of forming disciplinary identity (Brown et al, 2005;Gee, 2005). For this reason, investigating the attitudes and beliefs of scientists and emerging scientists is vitally important (Kagan, 1990).…”
Section: Attitudesmentioning
confidence: 99%
“…Sometimes we get a little closer. Like early anthropologists who visit the tribal village, we might get as far as the lab to observe and document their textual practices and the social and cultural contexts in which these practices take place (Bazerman 1988(Bazerman , 1998Doody, 2015;Graves, 2005). But we know little of how scientists think as writers-about their beliefs, attitudes and experiences of writing-even though learning to adopt the attitudes and beliefs of their seniors will be essential to our science students in the future as they develop both their professional identity and their fluency as disciplinary writers (Beaufort, 2007;Dall'Alba & Sandberg, 2006;Gee, 2005;Harding & Hare, 2000;Poe et al, 2010).…”
Section: Countries Not Often Heard Frommentioning
confidence: 99%